Expression And Characterization Of Recombinant Thermostable L2 Lipase In Pichia Pastoris - Sabri, Suriana (2007)
The gene encoding mature thermostable L2 lipase from Bacillus sp. L2 was cloned into Pichia pastoris expression vectors and placed under the control of the constitutive glyceraldehyde-3-phosphate dehydrogenase (GAP) promoter and methanol inducible alcohol oxidase (AOX) promoter. In inducible system, recombinant L2 lipase was efficiently secreted into the culture medium driven by the Saccharomyces cerevisiae α-factor signal sequence, compared to the constitutive system. The optimization of the recombinant L2 lipase production (from inducible system) in 100 mL culture was done for the best clones pPαS3 and pPαG2 from Pichia strains SMD1168H and GS115, respectively. The effect of media formulation, methanol concentration and induction time on L2 lipase production from inducible system was evaluated. A time course profile of recombinant lipase production in 500-mL flasks with the optimized conditions was performed and 15.3 mg/mL and 14.25 mg/mL of dry cell weight were produced after 144 h of induction time from recombinant pPαS3 and pPαG2, respectively. The lipase activities detected from both clones were 91 U/mL and 125 U/mL for pPαS3 and pPαG2, respectively. The recombinant L2 lipase was purified to 1.8-fold with 63.2% yield and with specific activity of 458.1 U/mg using affinity chromatography. The enzyme was in a monomeric form, non-glycosylated with a molecular weight of 44.5 kDa. The optimum pH and temperature were 8.0 and 70ºC, respectively. The enzyme was stable in the pH range of 8.0-9.0 and at 65ºC for 60 min where it retained more than 70% of its residual activity. The metal ions Ca2+, Na+, Cu2+ and Mn2+ activated the lipase at 1 mM, whereas Mg2+and Zn2+ inhibited it. Lipase showed a notable preference for medium to long chain triacylglycerols (C10–C16), with the highest activity toward tripalmitin (C16). It hydrolyzed all the natural oil tested, with the highest hydrolysis rate on corn oil and the least was on sunflower oil. L2 lipase was inhibited by EDTA, PMSF, pepstatin A and all the surfactants tested. It showed random positional specificity towards triolein. CD spectral analysis of L2 lipase revealed a Tm of around 67.2°C.